Cognitive impairment in children with 5q-associated spinal muscular atrophy type 1: two case reports and the review of the literature - Yang, Hua; Yang, Jie; Xue, Yawen; Liao, Lihui; Cai, Qianyun; Luo, Rong (Frontiers in Pediatrics, 2024)
Spinal muscular atrophy (SMA) is an autosomal recessive disease caused by mutations in the survival motor neuron 1 (SMN1) gene on chromosome 5, leading to the degeneration of lower motor neurons. There are few studies on cognitive impairment comorbid with SMA. Here, we report two cases of severe cognitive impairment in Chinese children with SMA type 1, marking the first such reports in this demographic. We propose that severe cognitive dysfunction may be a comorbidity of SMA. Clinicians should consider SMA in patients presenting with severe muscle weakness and atrophy accompanied by cognitive impairments, to avoid misdiagnosis and oversight.